Investment Project Analysis of Pt ABC External Power Electricity Interconnection With Utilities Power Generation System Pt Kilang Pt XYZ Internasional Refinery Unit III Plaju - Ardhi Septian (Green Publisher Indonesia, 2026)
PT Kilang PT XYZ Internasional is a company engaged in the business of refining petroleum into high-value products. The Plaju Refinery is a production facility in Palembang, with three (3) gas turbine generators in the utility section for electricity generation. The utility section of Refinery Unit III Plaju operates two gas turbines while one gas turbine is on standby, with a distributed load of 14 MW for the UA/UB GT and 10 MW for the UC GT. Both gas turbine generators operate below their design capacity (partial load), resulting in inefficiencies. High maintenance costs and the rising price of natural gas used in the gas turbine have resulted in high operating costs. This paper proposes improvements by implementing an external electricity interconnection project between PT ABC and the RU III Plaju utility. A SWOT analysis is used to evaluate internal and external factors influencing feasibility. Technical analysis aims to assess the feasibility of this project. Financial analysis is required to assess long-term profitability through projections of investment costs, operating costs, and potential cost savings. The financial feasibility analysis uses Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). Furthermore, the technical risk analysis refers to ISO 3100:2018 risk assessment procedures, and the financial analysis uses Monte Carlo simulations. The technical analysis results indicate that this project can be implemented with an operational integration configuration: one 12 MW gas turbine-generator and 12 MW of external PT ABC electricity.